POTENTIAL DRUG-DRUG INTERACTIONS IN PSYCHIATRIC PATIENTS DURING HOSPITALIZATION AND AT HOSPITAL DISCHARGE - Koraliya Todorova-Nenova; Maria Zhelyazkova-Savova; Silvia Gancheva; Elitsa Stoychev (Peytchinski Publishing, 2022)
Purpose: The present study aimed to evaluate the frequency of pDDIs in male patients admitted to a university-based intensive psychiatric unit over a twelve-month period and to assess patients' exposure to pDDIs as inpatients and potential outpatients. Material/Methods: Charts of 425 consecutive hospitalized patients with psychiatric disorders were reviewed. Potential DDIs were assessed and categorized using Lexicomp® drug interaction software. Statistical analyses were performed with IBM SPSS Statistics for Windows, Version 20.0. Results: A total of 1404 pDDIs (3.3 per patient) were identified for the hospitalization period. Categorized in risk rating categories X and D, considered most relevant for the safety of the patients were 346 (24.64%) of them. Among the pharmacodynamic pDDIs, most frequent were pDDIs associated with central nervous system depression, followed by QT‐interval prolongation. Hospital discharge prescriptions included 631 pDDIs (1.48 per patient). Out of them, 144 (22.82%) were identified in risk rating categories X and D. Among the pharmacodynamic pDDIs first in frequency were pDDIs related to QT-interval prolongation, followed by pDDIs associated with central nervous system depression. Potential DDIs that could lead to serotonin syndrome or extrapyramidal side effects were relatively infrequent during hospitalization and at discharge. No pharmacokinetic pDDIs were categorized in groups X and D. Conclusions: The study showed a higher frequency of pDDIs during the hospitalization period compared to hospital discharge with no change of the nature of the potential risks for the safety of the patients. Caution is warranted to limit the exposure of the patients to pDDIs.